Assessment of eukaryotic diversity around Robert Island in Antarctica by metabarcoding - Tarhana, Yağmur. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2022., 2022)
The rapid growth of human population and overuse of natural resources lead to the deterioration of the balance of ecosystems. Disruption of the environment adversely affects biodiversity and can even cause species extinctions. Since the traditional species detection methods can be expensive and time-consuming, a new, cost-effective, and environmental- friendly method has emerged as an alternative. The new environmental-DNA (eDNA) metabarcoding method is based on DNA isolation, amplification of barcode region, and sequencing of samples taken from environmental systems followed by data analysis for taxonomic assignment. In this study, water samples were collected around Robert Island in Antarctica as a part of the second Turkish Antarctic Expedition (TAE-II) in 2018 to monitor species diversity. Then, mitochondrial cytochrome oxidase I (COI) barcode regions were amplified and sequenced on Illumina platform. Sequences were formatted via OBITools, aligned with BLAST+, and compared with three reference databases (MIDORI, WoRMS, and GenBank) for taxonomic assignment. A total of 39 taxa were found, of which 18 were identified as animal species, but most of the species were algae. Identifying only one taxon in common in the three databases revealed the inconsistency between the reference databases. Additionally, 166 OTUs in MIDORI and 179 OTUs in WoRMS and GenBank databases remained unidentified, indicating that they are deficient in terms of the reference sequence information of taxa found in Antarctica. We conclude that various methods and databases should be used in tandem for biodiversity characterization via metabarcoding in order to increase accuracy and capture species diversity, at least in Antarctica.
Keywords: Eukaryotic cells.; Metabarcoding.